Decarbonization scenarios of the U.S. Electricity system and their costs. (1st November 2022) - Qiu, Yang; Cohen, Stuart; Suh, Sangwon
Highlights: Pursuing a zero-carbon US electricity system would incur additional cost. The use of non-renewable low-carbon resources reduces the additional cost. Negative emission technologies show economic advantage to mitigate the last few percent CO2 from the US electricity system. Abstract: Decarbonizing the electricity system to zero-carbon emission is crucial for climate change mitigation. Previous studies have shown that such a transition in the United States (U.S.) may lead to higher system cost compared to a business-as-usual case, but it is not well-known how the cost of electricity generation varies at sub-regional level under the transition, and studies have rarely evaluated the trade-off between the cost and avoided climate damages, as well as the potential roles of negative emission technologies (NETs) in the electricity decarbonization. Here, we present a regionally resolved national model to quantify the cost of decarbonizing the U.S. electricity system under a set of possible scenarios. The results show that, compared to the reference scenario without a decarbonization policy, reaching zero CO2 emission by 2050 would incur, depending on the scenarios, 335–494 billion USD additional cost to the U.S. electric power sector during 2020–2050. The regional costs of electricity generation ranges from 2.4 to 4.7 cent/kWh, largely due to the generation profiles and renewable resources availability of those regions. The additional costs can be translated to an average CO2 abatement cost of 29–59 USD/metric ton CO2 (with 2%–7% discount rates), which are comparable to the social cost of carbon in the literature at around 4% discount rate. The results also show that the cost of mitigating the last few percent CO2 emission from the U.S. electricity system may exceed the costs of NETs, indicating an opportunity for NETs to contribute to electricity decarbonization.